Reduction of Total Coliform, Ammonia (NH3-N), and COD Levels in Liquid Waste from the IPLT Keputih Using a Combination of H2O2-UVC - Rizky Maulida Annisafitri; Mohamad Mirwan; Rizka Novembrianto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Population growth in Indonesia poses sanitation challenges, where Sewage Sludge Treatment Plants (IPLT) provide a solution for sewage waste treatment. However, IPLTs themselves still face obstacles in optimally removing contaminants such as ammonia, Total coliform bacteria, and COD. This study evaluates the effectiveness of advanced oxidation processes (AOPs) combining hydrogen peroxide and ultraviolet light (H2O2-UV) in degrading these three pollutants. The wastewater used in this study came from the outlet of the Final Clarifier unit. The experiments were conducted in a continuous reactor with varying concentrations of H2O2 (0.1%-0.7%) and UV light contact time (15-45 minutes). The results showed that the highest degradation efficiency was achieved at a H?O? concentration of 0.7% for 45 minutes, with a removal percentage of 99.24% for Total Coliform bacteria and 88.32% for Ammonia. However, for COD, the highest degradation efficiency was achieved at a concentration of 0.5% for 45 minutes with a removal percentage of 79.55%. These results prove that the H2O2-UV process is effective in degrading IPLT wastewater pollutant mixtures through the production of non-selective hydroxyl radicals (•OH).